Medical decision analysis for first-line therapy of chronic myeloid leukemia. Issue 8 (August 2014) - Rochau, Ursula; Sroczynski, Gaby; Wolf, Dominik; Schmidt, Stefan; Conrads-Frank, Annette; Jahn, Beate; Saverno, Kim; Brixner, Diana; Radich, Jerald; Gastl, Guenther; Siebert, Uwe
Abstract Several tyrosine kinase inhibitors (TKIs) are approved for the treatment of chronic myeloid leukemia (CML). Our goal was to develop a clinical decision-analytic model for evaluation of the long-term effectiveness of different therapy regimens. We developed a Markov cohort model with a lifelong time horizon for first-line treatment with imatinib, dasatinib or nilotinib. Seven strategies including combinations of TKIs, chemotherapy and stem cell transplant were evaluated. The model was parameterized using published trial data, the Austrian CML registry and practice patterns estimated by experts. Health outcomes evaluated were life-years (LYs) and quality-adjusted LYs (QALYs). Based on our decision analysis, dasatinib following nilotinib failure was the most effective treatment in terms of LYs (19.8 LYs) and QALYs (16.1 QALYs). Sensitivity analyses showed that the ranking of strategies was mostly influenced by the duration of first- and second-line therapies. Our results may support decision-making regarding the sequential application of TKIs.